Movement-associated proteins of potato virus A : attachment to virus particles and phosphorylation - Gabrėnaitė-Verkhovskaya, Rasa (University of Helsinki, 2007)
Tiivistelmä.
Keywords: kasvitaudit; virustaudit; viljelykasvit; virukset; proteiinit